Blue Restoration – Building Confidence and Overcoming Barriers - Stewart-Sinclair, Phoebe J.; Purandare, Jemma; Bayraktarov, Elisa; Waltham, Nathan; Reeves, Simon; Statton, John; Sinclair, Elizabeth A.; Brown, Benjamin M.; Shribman, Zoë I.; Lovelock, Catherine E. (Frontiers in Marine Science, 2020)
Marine coastal (or ‘blue’) ecosystems provide valuable services to humanity and the environment, but global loss and degradation of blue ecosystems necessitates ecological restoration. However, blue restoration is an emerging field and is still relatively experimental and small-scale. Identification of the key barriers to scaling-up blue restoration will enable targeted problem solving and increase the likelihood of success. Here we describe the environmental, technical, social, economic, and political barriers to restoration of blue ecosystems, including saltmarsh, mangroves, seagrass, shellfish reefs, coral reefs, and kelp forests. We provide managers, practitioners, and decision-makers with solutions to construct barrier-informed blue restoration plans and illustrate these solutions through the use of case studies where barriers were overcome. We offer a way forward to build confidence in blue restoration for society, government, and restoration practitioners at larger and more ambitious scales.